2013
DOI: 10.1134/s0020168513080189
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen release from SrCo0.8Fe0.2O3 − δ

Abstract: We have studied oxygen release from a membrane material with the composition SrCo 0.8 Fe 0.2 O 3 -δ of various sizes in the temperature range 600-900°C in a flow reactor at oxygen partial pressures from 0.2 to 10 -5 atm. The results demonstrate that the oxygen release from samples 50 µm to 2 mm in size at temperatures above 800°C can be described in terms of a quasi equilibrium model. For fine powders, ≤63 µm in size, the tem perature range of quasi equilibrium oxygen release begins at t ≥ 600°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The Fe-based perovskite-type oxides are also considered to be one of the most promising materials as an oxygen sorbent due to their excellent oxygen sorption/desorption properties. Previous studies on an oxygen sorbent for the HT-PSA process have revealed that the Fe-based perovskite-type oxides, such as Sr–Fe–O, Ba–Fe–O, Ba–Sr–Fe-O, La–Sr–Co–Fe-O, ,, Sr–Co–Fe-O, , and Ba–Sr–Co–Fe-O, exhibit rather high oxygen sorption/desorption capacity at high temperatures. These materials work well as an oxygen sorbent in a pressure-swing process between air and a sweep gas, e.g., N 2 (or He), whose oxygen concentration is at the ppm level or below.…”
Section: Introductionmentioning
confidence: 99%
“…The Fe-based perovskite-type oxides are also considered to be one of the most promising materials as an oxygen sorbent due to their excellent oxygen sorption/desorption properties. Previous studies on an oxygen sorbent for the HT-PSA process have revealed that the Fe-based perovskite-type oxides, such as Sr–Fe–O, Ba–Fe–O, Ba–Sr–Fe-O, La–Sr–Co–Fe-O, ,, Sr–Co–Fe-O, , and Ba–Sr–Co–Fe-O, exhibit rather high oxygen sorption/desorption capacity at high temperatures. These materials work well as an oxygen sorbent in a pressure-swing process between air and a sweep gas, e.g., N 2 (or He), whose oxygen concentration is at the ppm level or below.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies on the oxygen separation using SrCo x Fe 1– x O 3−δ have been focused on improvement in oxygen permeation property or stability of SrCo x Fe 1– x O 3−δ , by substituting an A-site or B-site cation with other metal ions. On the other hand, for application of an oxygen sorbent for the HT-PSA process, Lin et al have first proposed that the perovskite-type oxides such as La y Sr 1– y Co x Fe 1– x O 3−δ can be used as an oxygen sorbent for the HT-PSA process. , The perovskite-type oxide can sorb and desorb oxygen largely and reversibly by changing ambient partial pressure of oxygen, resulting in separation of oxygen from air. The subsequent studies on the oxygen sorption/desorption properties demonstrated that the Co–Fe-based perovskite-type oxides usually gave relatively good behavior. ,,, In addition, fundamental research involving the oxygen nonstoichiometry for SrCo x Fe 1– x O 3−δ , influencing both oxygen membrane-permeation property and oxygen PSA sorption/desorption properties, has been conducted over the past decades. Although SrCo x Fe 1– x O 3−δ species have often been examined in the oxygen-permeation membrane tests, an oxygen separation test from air using the HT-PSA apparatus loaded with SrCo x Fe 1– x O 3−δ sorbent is limited to our preliminary research report . Thus, in this study, we aim to evaluate oxygen sorption/desorption properties of SrCo x Fe 1– x O 3−δ , and we examined the preliminary oxygen-production test by using a small-scale PSA apparatus, especially operateing at lower temperature like 300 °C.…”
Section: Introductionmentioning
confidence: 99%